ПОЗИЦИОНИРОВАНИЕ И КОНКУРЕНТОСПОСОБНОСТЬ РЕГИОНОВ В ПРОЦЕССЕ СОЦИАЛЬНО-ЭКОНОМИЧЕСКОГО РАЗВИТИЯ (Географический вестник=Geographical bulletin, 2017)
На основе анализа отечественных источников рассматривается проблема позиционирования и конкурентоспособности регионов России в процессе социально-экономического развития. Предлагается собственная концепция конкурентоспособности, определяются её детерминанты и показатели. По авторской методике проводится оценка конкурентоспособности регионов, входящих в Приволжский федеральный округ.POSITIONING AND COMPETITIVE ABILITY OF REGIONS IN THE PROCESS OF SOCIO-ECONOMIC DEVELOPMENTAs the result of transition to postindustrial stage of social development and widening enlargement of global interaction, the competition for possession of different resources of socio-economic development is raised between the individual states and the regions. This problem is usual for Russia, as an important “player” in the world economy. The authors of the abstract have analyzed official documents and scientific literature, in which versions of our state’s development in XXI century, opportunities of positioning and using it competitive advantages in marked processes are considered. Also, they have given comparison of Russian and western models of post industrialism.After the critical estimation of different positions the authors had no conclusion, that modern conceptions of competitive ability that can not be based on the economic aspects only. They should be considered through four main systems: population, economy, infrastructure, nature and ecological situation. The general aim of these conceptions must be constant increasing of life’s quality of the territorial community of people (TOP) and the development of social sphere of person’s activity.The authors have offered own conception of competitive ability, which includes principals and determinants of socio-economic development, their interactions and links between themselves, selected by four basic components: economic, territorial (geographical), natural-ecologic and socio-demographic ones. Twelve indexes, characterized these components, are chosen. The methods of comparative ability’s estimation are proved.The final stage of the research includes the ranging of regions, included in Privolzhskiy Federal district, on the degree of their competitive ability.